Solve the following homogeneous differential equation 2x3 y' = y(2x2 − y2)
"2x^3y'=2x^2y-y^3\\\\\n\\frac{dy}{dx}=\\frac{2x^2y-y^3}{2x^3}\\\\\n\\text{put\\,} y=vx\\\\\nv+x\\frac{dv}{dx}=\\frac{2v-v^3}{2}\\\\\nv+x\\frac{dv}{dx}=v-\\frac{v^3}{2}\\\\\nx\\frac{dv}{dx}=-\\frac{v^3}{2}\\\\\n2\\frac{dv}{v^3}=-\\frac{dx}{x}\\\\\n\\frac{-1}{v^2}=-lnx+c\\\\\nv^2=\\frac{-1}{c-lnx}\\\\\n\\frac{y^2}{x^2}=\\frac{1}{lnx+C}\\space(put\\space C=-c)\\\\\n\\text{This is the required solution.}\n\\\\"
Comments
Leave a comment